Analisis Faktor-Faktor Yang Mempengaruhi Harga Saham (Systematic Literature Review) - Miyandini, Regita (CV. Kalimasada Group, 2024)
Shares are documents or securities that prove ownership of a company. Shares are one of the capital market assets that investors are most interested in. Given the many options available to them when allocating their capital, investors must consider the factors that will influence their careful calculations. Therefore, it is important to understand the variables that influence stock value better. The aim of this research is to find out what factors influence stock prices. The research method used a systematic literature review by obtaining 11 articles for review based on Sinta indexed articles from 2017-2023. The results obtained show that the factors that can influence stock prices are the rupiah exchange rate, trading volume, managerial ownership, profitability, company size, intangible assets, earnings per share, return on assets, debt to equity ratio, return on equity, book value per share, dividend per share, capital structure, company growth, financial leverage, dividend policy, these factors are obtained based on the results of a review of quantitative research which has been proven significantly